Writing the Self: Interior Voyage in 19th Century French Travel Writing - Andi Mustofa; Wening Udasmoro; Sri Ratna Saktimulya (Universitas Sanata Dharma, 2023)
Travel is a momentum to look inside that influences the travelers' existence, along with meeting and interacting with others. The self as a traveler experiences internal dynamics reflected in the travel writings. This paper analyzes five French travel writings to reveal the self-construction of travelers who explored the East in the 19th century. The analysis results show that travelers’ self-construction is divided into Enlightenment or Romantic subjects and true travelers or travelers as tourists. The Enlightenment subject prioritizes facts and empirical knowledge outside of the self for the broader interest. In contrast, the Romantic subject puts forward subjective and emotional attitudes in dealing with and narrating others used for personal gain. True travelers look for difficulties in other places to prove themselves in conquering the challenges. Travelers as tourists try to avoid the obstacles by seeking safety and comfort during the trip. The East as a travel destination is a space that offers difficulties in constructing and legitimizing the traveler's self-image with the attributes that society expects, such as courage and persistence. The five French travelers, both Enlightenment or Romantic subjects and true travelers or tourists, had various knowledge of the others due to factors such as the purpose of the trip, profession, social status, and duration of the trip. Knowledge of the others and self-disclosure narrated in travel writings manifest the French travelers’ power to control and manage themselves and represent the Other.